2022
DOI: 10.3390/ijms23115904
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-Amino-3-oxo-2,7-naphthyridines via Smiles Rearrangement: A New Approach in the Field of Chemistry of Heterocyclic Compounds

Abstract: In this paper we describe an efficient method for the synthesis of new heterocyclic systems: furo[2,3-c]-2,7-naphthyridines 6, as well as a new method for the preparation of 1,3-diamino-2,7-naphthyridines 11. For the first time, a Smiles rearrangement was carried out in the 2,7-naphthyridine series, thus gaining the opportunity to synthesize 1-amino-3-oxo-2,7-naphthyridines 4, which are the starting compounds for obtaining furo[2,3-c]-2,7-naphthyridines. The cyclization of alkoxyacetamides 9 proceeds via two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We synthesized terminal alkines from the 3(6)-hydroxy derivatives of cyclopenta[ c ]pyridine 1a [ 25 ], 5,6,7,8-tetrahydroisoquinolines 1b – d [ 25 ], pyrano [3,4- c ]pyridines 1e – g [ 14 , 26 ], and 2,7-naphtyridines 1h , i [ 27 ] to obtain the aimed hybrids, the 1,2,3-triazoles. It should be mentioned that tautomerism is possible in compound 1 lactam-lactim (NH/OH) via proton-migration of a hydrogen atom between the two basic centers.…”
Section: Resultsmentioning
confidence: 99%
“…We synthesized terminal alkines from the 3(6)-hydroxy derivatives of cyclopenta[ c ]pyridine 1a [ 25 ], 5,6,7,8-tetrahydroisoquinolines 1b – d [ 25 ], pyrano [3,4- c ]pyridines 1e – g [ 14 , 26 ], and 2,7-naphtyridines 1h , i [ 27 ] to obtain the aimed hybrids, the 1,2,3-triazoles. It should be mentioned that tautomerism is possible in compound 1 lactam-lactim (NH/OH) via proton-migration of a hydrogen atom between the two basic centers.…”
Section: Resultsmentioning
confidence: 99%
“…13−15 2,7-Naphthyridines occupy a special place in our research in the field of the synthesis of fused heterocyclic systems -in our previous papers we have examined their reactivity with several amines and found a new unexpected rearrangement, 16,17 other chemical transformations leading to heterocyclizations 18,19 and an azide-tetrazole equilibrium. 20 Furthermore, in an our recent paper we successfully synthesized furo[2,3-c]-2,7naphthyridines 21 whose synthesis until recently failed. Some of these investigations revealed that bicyclic 1,3dihydroxy-2,7-naphthyridines showed antiarhythmic activity, 22 while tricyclic pyrazolo [3,4-c]-2,7naphthyridines 23 and triazolo [3,4-a]-, as well as some triazolo[5,1-a]-2,7-naphthyridines, 24 displayed high neurotropic activity.…”
Section: Introductionmentioning
confidence: 99%